Bi-Hamiltonian structure of the extended noncommutative Toda hierarchy. Issue 3 (2nd July 2016) - Li, Chuanzhong; Song, Tao
Abstract : The noncommutative Toda hierarchy is studied with the help of Moyal deformation by a reduction on the non-commutative two dimensional Toda hierarchy. Further we generalize the noncommutative Toda hierarchy to the extended noncommutative Toda hierarchy. To survey on its integrability, we construct the bi-Hamiltonian structure and noncommutative conserved densities of the extended noncommutative Toda hierarchy by means of the R-matrix formalism. This extended noncommutative Toda hierarchy can be reduced to the extended multicomponent Toda hierarchy, extended ZN -Toda hierarchy, extended Toda hierarchy respectively by reductions on Lie algebras.